Trade-offs among competing uses of a Malaysian forested catchments - Mohd Shahwahid, H.O.; Awang Noor, A.G.; Abdul Rahim, N.; Zulkifli, Y.; Razani, U. (Cambridge University Press (CUP), 1999)
In this project, an attempt is made to estimate the costs and benefits of managing forested catchments in Malaysia. Three land use options are simulated for four selected catchments in the Hulu Langat Forest Reserves (HLFR), Selangor, Malaysia. These options are no logging or catchment protection (CP), reduced impact logging (RIL) and conventional logging (CL). The potential sedimentation impacts of each option on the dam and water intake ponds in the catchments are calculated. The benefits derived from logging, hydro-electric power (HEP) generation and the water regulatory dam for water treatment and the external costs emanating from the sedimentation under the three options are estimated. The computations are based on data collected from previous studies conducted in adjacent areas with similar hydrological parameters, secondary data from published reports by various departmental agencies and from on-site personnel surveys. Analysis at the compartment level suggests that the central issue of joint production in forested catchments is not the selection of which logging methods to adopt. Rather the point is which water use can be combined with timber production that can generate greater NPV than the status quo CP option. Under both logging methods, the returns from timber cannot meet that from the status quo production of treated water. Complementing water uses with logging in forested catchments is efficient in HEP catchments. The efficient choice among the two logging methods is the RIL option because of its higher returns and the lower externality imposed upon the status quo water user. However, despite the imposition of conservational measures, the RIL option still generates sediment loads that impose substantial external costs on the downstream water users. This analysis does not incorporate the effects of the alternative logging options on the other attributes of natural forests such as recreation, bio-diversity values and non-timber forest products (NTFP).